Comunicação pública e promoção da saúde: estudo de campanhas de prevenção de ISTs entre jovens - Lobo, Estela Cavalheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The exercise of sexual citizenship, especially by young people, is an indisputable right that must be promoted. Public communication for health should seek to disseminate the necessary basic information that can guarantee the social and health well-being of the young population in the development phase. This final paper presents the results of the analysis of campaigns for the prevention of sexually transmitted infections (STIs) aimed at the young population carried out by the federal, state and municipal governments over a 10-year period in the country (2010– 2019). The analysis was performed using an evaluation instrument that marks the presence or absence of quality attributes for health-promoting communication, according to aspects selected from the specialized literature. The results obtained suggest that the communication produced by public agencies over the monitored period is still superficial and mostly not very deep. The communication pieces best evaluated by the instrument have characteristics in common: the protagonism of young people to illustrate the narratives, the diversity of people, relationships and contexts, and the incentive to the young person's right to choice and autonomy. However, in general, a large part of the sample is marked by approaches that express simplified orders that leave informational gaps about STI prevention and do not seek to establish a dialogue.

O exercício da cidadania sexual, sobretudo pelos jovens, é um direito incontestável que deve ser promovido. A comunicação pública para saúde deve buscar a divulgação das informações básicas necessárias que possam garantir o bem-estar social e de saúde da população jovem em fase de desenvolvimento. Este trabalho de conclusão de curso apresenta os resultados de análise de campanhas de prevenção de infecções sexualmente transmissíveis (ISTs) voltadas para a população jovem realizadas pelos governos federal, estaduais e municipais dos últimos 10 anos no país (2010–2019). A análise foi realizada a partir de um instrumento avaliativo que marca a presença ou ausência de atributos de uma comunicação promotora da saúde com qualidade, conforme aspectos selecionados da literatura especializada. Os resultados obtidos sugerem que a comunicação produzida pelos órgãos públicos ao longo do período monitorado ainda é superficial e pouco aprofundada em sua maioria. As peças de comunicação mais bem avaliadas pelo instrumento possuem características em comum: o protagonismo do jovem para ilustrar as narrativas, a diversidade de pessoas, relacionamentos e contextos, e o incentivo ao direito à escolha e autonomia do jovem. No entanto, de maneira geral, grande parte da amostra é marcada por abordagens que exprimem ordens simplificadas que deixam lacunas informacionais acerca da prevenção de ISTs e não buscam estabelecer diálogo.
Public communication and health promotion: study of STIs prevention campaigns among young people
Keywords: Public communication; Health campaigns; Sexual rights; Young population; Comunicação; Campanhas de saúde; Promoção da saúde; Direitos sexuais; População jovem; Jovens